Environmental Risk and Management of Herbal-Extraction Residues Induced by the Composition and Metal Binding Properties of DOM - Yuan, Donghai; Cui, Yanqi; Kou, Yingying; Guo, Xujing; Chen, Bin (Frontiers in Environmental Science, 2022)
As the consumption of Chinese medicine resources increases, the waste of traditional Chinese medicine extraction cannot be disposed of reasonably, which has a serious impact on the environment. Dissolved organic matter (DOM), a crucial fraction in herbal extraction residue, can bond to heavy metals (HMs), creating a potential environmental risk. This study investigated the binding property of herbal extraction residue DOM with Cu(II) via two-dimensional Fourier transform infrared (FTIR) and synchronous fluorescence correlation spectroscopy (2D-COS) in conjunction with parallel factor (PARAFAC) modeling. Through PARAFAC analysis, three kinds of protein components and one kind of fulvic acid can be obtained, and protein-like substances are dominant in the residual DOM of Chinese medicine extracts, becoming the main factor of water quality deterioration. A fluorescence quenching experiment shows that protein-like materials provide the primary binding sites with Cu(II). During the detection, the long-wavelength low-intensity signal will be obscured. The 2D-COS obtained by the 1/9th power transformation can enhance the fluorescence signal so as to get even more information about the binding sites and heterogeneity of DOM and heavy metal ion ligands. The N−H of amine in the protein-like materials could prioritize combining with Cu(II). This study urges that continuous and effective attention be paid to the impact of the herbal extraction residue on the geochemical behavior of HMs.